Pengaruh Kombinasi Genggam Jari dan Aromaterapi Jasmine Terhadap Nyeri Pasien Post Operasi Sectio Caesarea - Triana Dewi Utaminingsih; Rika Agustina; Zuli Misnawati; Puput Sandiana (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Mothers with sectio caesarea will experience several problems such as pain, impaired mobility and anxiety. The pain felt by the mother of Sectio Caesarea can come from the incision scar under the abdomen. However, the severity of pain experienced by the mother will differ depending on the psychological and physiological as well as the pain tolerance experienced by the mother. Non-pharmacological therapies that can be given to reduce pain are a combination of finger grips and Jasmine aromatherapy. The method used in this study is a descriptive case study design with a case study approach based on the application of evidence-based practice of giving a combination of finger grip with jasmine aromatherapy. The sample of 2 people in this study was mothers after sectio caesarea surgery. This case study was conducted in June 2022. The measuring instrument uses a numerical pain intensity scale. The results obtained from both pain subjects can decrease from moderate pain decreased to mild pain. There was a reduction in pain after a combination of finger grips and Jasmine aromatherapy in post-sectio caesarea mothers. Suggestions for the public are expected to be able to independently apply finger gripping techniques with a combination of jasmine aromatherapy in reducing pain.